Characterization and evaluation of sorption potential of the iron mine waste after Samarco dam disaster in Doce River basin – Brazil - Almeida, Cristiane Aparecida; Oliveira, André Fernando de; Pacheco, Anderson Almeida; Lopes, Renata Pereira; Neves, Antônio Augusto; Queiroz, Maria Eliana Lopes Ribeiro de (Chemosphere, 2018)
The Fundão dam collapsed releasing 60 million tons of mining waste into the environment. The mining wastes should be better studied, since some of them are deposited on the alluvial plains soil and at the bottom of the rivers, like sediments, of the region affected. Thus, this work aims to perform the chemical, physical and adsorptive characterization of the samples colleted in region de Paracatu de Baixo. The mining waste has uneven surface, with sizes ranging from 2 to 200 μm, pHPCZ in 6.0. Are composed predominantly by kaolinite, goethite, hematite, gibbsite and quartz. It has been classified as non-hazardous residues. The adsorption studies showed the mining waste have a low Cationic Exchange Capacity. The sorption process was occurs by ion exchange and the kinetics follows the pseudo second order model (R2 > 0.78). The process is endothermic (ΔH in 29.33 kJ mol−1) and spontaneous (ΔG in −24.7 kJ mol−1 at 25 °C). The Langmuir model presented a better fit (R2 > 0.995) to the experimental data. Therefore, the methylene blue can be used as a cation model to predict the behavior of cationic species on the mining waste, with maximum adsorption capacity of 4.42 mg g−1 at 25 °C.
Keywords: Environment; Cationic dye; Kinetics; Mining wastes